Seed removal by Dorymyrmex insanus (Hymenoptera: Formicidae) in an ecological reserve in Mexico City, Mexico - Salazar Reyes, Cecilia; Ríos-Casanova, Leticia (Revista de Biología Tropical, 2022)
Introduction: Seed removal by ants is an interaction that may greatly affect the dynamic and structure of the vegetation. This aspect is well known for granivorous ants; however, there is little information on the effect of omnivorous ants. Objective: To assess the potential impact of the omnivorous ant Dorymyrmex insanus on vegetation. Methods: In the Pedregal Reserve, Mexico City, we identified the items in the refuse piles of ten ant colonies, for one year, covering the rainy and dry seasons. For each season we calculated seed diversity and analyzed the possible relationship between seed size and their abundance in the refuse piles, with regression models. We also did germination tests with seeds of Tagetes micrantha, comparing seeds from piles and from plants. Results: D. insanus removed seeds of 19 plant species as well as plant remains (such as leaves, twigs, roots), and remains of insects. Seed diversity was higher in the rainy season but the greatest abundance was in the dry season. When analyzing the relationship between seed length and abundance in the refuse piles, we found that the ants preferred seeds of around 10 mm. We also found that more seeds of T. micrantha germinated when they were previously handled by ants. Conclusions: The ant D. insanus actively participates in the removal of seeds from several species, favoring germination, and seasonality affects the selectivity of resources.